2021
DOI: 10.1002/admt.202100797
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Powered Gyroscope Angle Sensor Based on Resistive Matching Effect of Triboelectric Nanogenerator

Abstract: Progressive improvements of the Internet of Things (IoT) promote the sustainable development of the modern information society. [1,2] When the IoT is an analogy to the human sense as a means to immediately acquire precise environmental information, the large-scale and widely distributed sensor networks are similar to synaptic terminals, which are available to accurately realize various functions of intelligent identification, positioning, tracking, monitoring, and management. Among them, motion sensors, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…It was found that as the frequency increased from 1 to 6 Hz, the peak V OC increased from 209.7 to 542.6 V. The enhanced peak V OC can be ascribed to improved contact−separation rate between different friction materials, inducing a greater amount of triboelectric charges in the same period. 46,47 Figure 5i presents the output voltage of the KLP under different applied forces. With the increase of applied force from 20 to 45 N, the peak V OC increased from 247.1 to 621.2 V. This is because the larger applied force could enhance the effective contact area between the different friction materials, resulting in more transferred charges.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that as the frequency increased from 1 to 6 Hz, the peak V OC increased from 209.7 to 542.6 V. The enhanced peak V OC can be ascribed to improved contact−separation rate between different friction materials, inducing a greater amount of triboelectric charges in the same period. 46,47 Figure 5i presents the output voltage of the KLP under different applied forces. With the increase of applied force from 20 to 45 N, the peak V OC increased from 247.1 to 621.2 V. This is because the larger applied force could enhance the effective contact area between the different friction materials, resulting in more transferred charges.…”
Section: Resultsmentioning
confidence: 99%
“…However, inertial sensors based on self-power need an external monitoring circuit. To decrease complexity and improve stability and sensitivity, Xie et al [ 74 ] proposed a gyroscope based on the impedance matching effect of TENG for measuring relative rotation angle, containing a freestanding-mode rotary dis-shaped triboelectric nanogenerator, a resistive rotation angle sensor, and a light-emitting diode (LED) alert display, with a high sensitivity of (67.3 mv −1 ), good linearity between the output voltage and the rotation angle, and quick response of 20 ms in the range of 0~260°. At the same time, the device removed the batteries and management circuits to simplify the system and used the quantized LED to display the rotation angles.…”
Section: Biophysical Signalsmentioning
confidence: 99%
“…Liyun Ma et al [ 45 ] developed smart protective clothing based on triboelectric nanogenerators, which collect motion to power the monitoring system. Xinkai Xie et al [ 46 ] utilized TENG to design a self-powered gyroscope angle sensor to detect the relative rotation angle. Song Wang et al [ 47 ] designed a self-powered tilt sensor based on an SL-TENG, which demonstrates stable output and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%